Compact Wilkinson Power Divider Using Composite Right/Left-Handed Transmission Line on CMOS Process - Nithiporndecha, Kittipong; Wang, Sen; Pakasiri, Chatrpol (My University, 2020)
This paper shows the design and analysis of CMOS Wilkinson power divider using composite right/left-handed transmission lines. The effects of lossy components in the circuit are also analyzed. The circuit is then implemented on a 0.18-μm CMOS process. The return losses are less than -16 dB, the isolation is better than -26 dB, and the insertion losses are better than -5.15 dB at the frequencies of interest. Its chip size is 0.5 mm2 (9.9e-5λo2) including testing pads.
Keywords: CMOS; composite right/left-handed transmission line; lossy substrate; Wilkinson power divider